DEIKSIS DALAM FILM BEAUTY AND THE BEAST KARYA JEANNE-MARIE LEPRINCE DE BEAUMONT - SUMAKUL, IRLANI NIKITA MEGAWATI; JANSEN, FRIEDA TH.; RAMBING, ROSALINA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTÂ Â This research entitled â€œDeiksis dalam film Beauty and The Beast by Jeanne-Marie Leprince De Beaumontâ€. Is written to identify, classify and analyze the types and how deixis used in the film Beauty and The Beast by Jeanne-Marie Leprince De Beaumont. The method that used in this research is the descriptive method, and the data taken from film Beauty and The Beast by identify and classifying deixis according to their types and usage . The data have been analyzed using the theory of Levinson. The types of deixis that found in the film Beauty and The Beast by Jeanne-Marie Leprince De Beaumont Â are person deixis (first person,second person and third person), place deixis, time deixis, discourse deixis and sosial deixis and the usage of deixis that is gestural and symbolic. Theoretically, this research is intended to add to the research of linguistic research, especially in the field of pragmatics about deixis. Practically, it is expected to be a comparative material for other researchers who will analyze the same thing in linguistic field, and can provide information to increase readerâ€™s knowledge on linguistic especially deixis.__________________Keywords: Deixis, Pragmatics, Film:Beauty and The Beast.Â